Anticandidal and antioxidant potencies of endophytic fungi associated with Tinospora crispa - AHMAD FATHONI; SUMI HUDIYONO; ANTONIUS HERRY CAHYANA; MUHAMMAD ILYAS; ISMU PURNANINGSIH; ANDRIA AGUSTA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fathoni A, Hudiyono S, Cahyana AH, Ilyas M, Purnaningsih I, Agusta A. 2023. Anticandidal and antioxidant potencies of endophytic fungi associated with Tinospora crispa. Biodiversitas 24: 2547-2555. Natural products including endophytic fungi, have opportunities for medicinal uses as anticandidal and antioxidant agents. This study aimed to investigate the anticandidal and antioxidant activities of endophytic fungi isolated from Brotowali (Tinospora crispa (L.) Miers ex Hook.fil. & Thomson) using disc diffusion, thin layer chromatography (TLC) dot-blot, and microdilution methods. Eighty extracts were screened for anticandidal activity against Candida albicans (C.P.Robin) Berkhout and antioxidants against 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radicals. Disc diffusion results showed that 38 endophytic fungi had an anticandidal activity with an inhibition zone diameter (IZD) of 7.00±00 to 18.1± 0.29 mm and 4 extracts with minimum inhibitory concentration (MIC) values of 32-64 µg/mL (strong, MIC<100). The TLC dot-blot results showed that 23 extracts had antioxidant activity and 8 extracts were very strong with an inhibitory concentration of 50% (IC50) values of 7.76±0.77 to 25.54±1.37 µg/mL, while the antioxidant activity index (AAI) values ranged from 2.01±0.10 to 6.64±0.63 (very strong, AAI>2). Results of the Pearson correlations coefficient between the total phenolic content (TPC) value and AAI value, revealed that there was a low correlation, while the correlation of IZD and MIC as anticandidal has a moderate negative (the r value 0.332, and -0.673, respectively (P<0.01). Purification of bioactive compounds is necessary, and endophytic fungi associated with T. crispa can serve as a potential source of natural antioxidants and anticandidal agents.